Malaysia's Young Adults' Perceptions And Attitudes Toward Entrepreneurship As A Career Choice - Sahari, Ahmad Mahir (2005)
This dissertation discusses the importance of entrepreneurship to a country, entrepreneurs' attributes and behaviour, and entrepreneurship as an alternative career choice. Reference is also made to current policy initiatives and entrepreneurship education in Malaysia.